Multidimensional evaluation of nutritional security policies in the Republic of Moldova: gaps, progress, and alignment with international standards - Rodica Siminiuc; Dinu Țurcanu; Sergiu Siminiuc (Frontiers in Public Health)
IntroductionNutritional security is increasingly recognized as a critical component of public health, particularly in addressing the growing burden of non-communicable diseases such as obesity, diabetes, and cardiovascular disease. In the Republic of Moldova, rapid changes in food availability and consumption patterns have intensified the need for robust public policies to promote healthy dietary habits.MethodsThis study evaluates Moldova’s public policies on nutritional security using a multidimensional model adapted from the Policy Evaluation Network framework. The model assesses five key policy categories: educational, strategic, labeling, monitoring, and fiscal policies, through a comprehensive 28-indicator structure.ResultsThe findings indicate that Moldova’s policy efforts in nutritional security are at a “satisfactory” level, with foundational strategies in place but significant gaps in policy cohesion, implementation, and monitoring. Educational and strategic policies show moderate progress, yet labeling, monitoring, and fiscal policies are underdeveloped, limiting their impact on public health.DiscussionThe results emphasize the need for a more coordinated, multi-sectoral approach, incorporating targeted fiscal incentives, systematic monitoring frameworks, and comprehensive educational reforms.